2023
DOI: 10.3389/fendo.2023.1193826
|View full text |Cite
|
Sign up to set email alerts
|

Association between duration of progesterone supplementation and clinical outcomes in artificial frozen-thawed embryo transfer cycles

Abstract: ObjectiveThe administration of progesterone before transfer in hormone replacement treatment (HRT) is crucial for the clinical outcomes of frozen-thawed embryo transfer (FET), but the optimal duration of progesterone remains controversial. This study aimed to investigate the effect of the duration of progesterone administration on the clinical outcomes of FET cycles.MethodsThis prospective cohort study included 353 artificial FET cycles conducted at a reproductive medicine center between April and October 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Other research has indicated that prolonged progesterone supplementation is linked to an increased incidence of biochemical pregnancy ( 32 ). However, the ideal length of time to use progesterone supplements remains a subject of debate, as prolonged supplementation might narrow the window of implantation, while a too-short period could raise the chance of losing a pregnancy too soon ( 32 35 ). Taken together, the intricate process of implantation comprises both intercellular and extracellular matrix interactions as well as spatiotemporally regulated endocrine, paracrine, and autocrine interactions ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other research has indicated that prolonged progesterone supplementation is linked to an increased incidence of biochemical pregnancy ( 32 ). However, the ideal length of time to use progesterone supplements remains a subject of debate, as prolonged supplementation might narrow the window of implantation, while a too-short period could raise the chance of losing a pregnancy too soon ( 32 35 ). Taken together, the intricate process of implantation comprises both intercellular and extracellular matrix interactions as well as spatiotemporally regulated endocrine, paracrine, and autocrine interactions ( 36 ).…”
Section: Discussionmentioning
confidence: 99%